Scanning electron microscopy of fruits in the West African polygonaceae (2010)
The fruit morphology of 18 taxa representing seven genera of the family Polygonaceae in West Africa was investigated using scanning electron microscopy. The achenes are trigonous, lenticular, globose, subglobose, heart shaped, ovoid, or cone like. Sizes range from 0.12 × 0.10 cm2 in Polygonum plebeium to 7.87 × 0.58 cm2 in Afrobrunnichia erecta. Colors are brown to black. The cells are isodiametric in P. plebeium, irregular in A. erecta, Antigonon leptopus, and Harpagocarpus snowdenii, and polygonal in other species. The walls are straight, curved, or undulate and are either raised or depressed. Afrobrunnichia erecta is characterized by deeply sinuate lateral walls. The cell surface may be smooth or tuberculate or fibrillate in the family, usually covered with wax deposits. The combination of these characters is mainly taxonomically useful at the tribal level and rarely at the specific or infraspecific level for the delimitation of the taxa.